The Supremacy of Peer Inclusion: An AI-Driven Vignette Experiment on Teamwork Dynamics - Soerjoatmodjo, Gita Widya Laksmini (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: Contemporary teamwork research remains heavily skewed toward leadership styles, often neglecting the horizontal influence of peer behavior. This study challenges the "heroic leader" paradigm by examining the impact of leader behavior (structured vs. open) and member behavior (inclusive vs. exclusive) on individual contributions. We utilized a novel 2 X 2 randomized vignette design, where scenarios were AI-generated to ensure high internal validity and eliminate researcher bias. Analyzing data from 375 participants, the results reveal a critical shift in teamwork theory: individual contributions are significantly driven by peer inclusiveness, whereas leadership styles—and the interaction between variables—yielded no significant effect. These findings suggest that in high-stakes collaborative environments, the "peer climate" overrides formal leadership directives. This research advocates for a paradigm shift in organizational training, moving away from top-down leadership development toward fostering "inclusive followership" as the primary driver of team effectiveness Keywords: Artificial intelligence, Group member behaviour, Leader behaviour, Teamwork, Vignette experiment